Groundwater oxygen anomaly related to the 2016 Kumamoto earthquake in Southwest Japan - SANO, Yuji (Proc Jpn Acad Ser B Phys Biol Sci, 2020)
Here, we report the groundwater oxygen isotope anomalies caused by the 2016 Kumamoto earthquake (M(JMA)7.3) that occurred in Southwest Japan on April 16, 2016. One hundred and seventeen groundwater samples were collected from a deep well located 3 km to the southeast of the epicenter in Mifune Town, Kumamoto Prefecture; they were drinking water packed in PET bottles and distributed in the area between April 2015 and March 2018. Further, the oxygen and hydrogen isotopes were evaluated via cavity ring-down spectroscopy without performing any pretreatment. An anomalous increase was observed with respect to the δ(18)O value (up to 0.51‰) soon after the earthquake along with a precursory increase of 0.38‰ in January 2016 before the earthquake. During these periods, there was no noticeable change in the hydrogen isotopic ratios. Rapid crustal deformation related to the earthquake may have enhanced the microfracturing of the aquifer rocks and the production of new surfaces, inducing δ(18)O enrichment via oxygen isotopic exchange between rock and porewater without changing δ(2)H.